How should economics view the Internet?. Issue 1 (14th September 2021) - Tao, Li
Abstract : Purpose: The study aims to elaborate the author's basic viewpoints on how economics should view the Internet from four aspects. Design/methodology/approach: This paper reviews the existing literature on this topic, and summarizes key findings and conclusions of these researches. Findings: The findings include four major contradictions in economics brought by the Internet, and 12 new changes in economics that needs to be addressed. Originality/value: This paper provides a clear summary of existing studies on economics' views of the internet and a prospect for future internet economy research.